KEMAMPUAN MENULIS TEKS PROSEDUR DENGAN MODEL DISCOVERY LEARNING PADA PESERTA DIDIK - Ningsih, Surya; Deliani, Susy; Zahara, Siti Fatima (Bahasa Indonesia Prima, 2023)
This research is motivated by the reality in the field to find out the application of discovery learning models to the ability to write procedural texts. This type of research uses a qualitative approach with experimental methods. The subjects of this study were all class XI MAS Al Washliyah 12 Perbaungan, with a total of 241 students. The object of this study was class XI IPA, which consisted of 31 students. In data collection techniques using tests, observations, questionnaires, and documentation. Meanwhile, data analysis was used to obtain scores in the form of results for student work on the ability to write procedural texts using the discovery learning model with an average value of 9.3. Therefore, the influence of the discovery learning model on the ability to write procedural texts has an average value of 9.3. Therefore, it can be concluded that the ability to write procedural texts using the discovery learning model for XI MAS Al Washliyah 12 students in the 2022-2023 academic year is said to have an effect with an average score of 9.3 with an excellent qualification of 86% -95%. Thus, based on the assessment that has been carried out, it can be explained that using the discovery learning model in the writing ability of students XI has the effect of the desired value.